This preview shows page 1. Sign up to view the full content.
Unformatted text preview: = P(A)P(B) then P(AB)= P(ABc) where P(B)and P(Bc) are not 0. a. Note:I could ask you to prove numbers of theorems we proved in our work with independence and conditional probability including independence of three events. You should be able to manipulate sets with set rules and use the definitions of conditional probability. 8. Suppose P(H2H1)=.3 and P(T2T1)=....
View Full
Document
 Spring '14
 Schneider
 Probability

Click to edit the document details